A high yielding and wilt resistant castor (Ricinus communis) hybrid for India - PATEL, A M; PATEL, D K; PATEL, C J; JAT, A L; SHAH, S K; TEJANI, D N; GANGWAR, G P; DESAI, A G (The Indian Journal of Agricultural Sciences, 2020)
The breeding efforts were made at Sardarkrushinagar (Gujarat) during 2006-07 to 2015-16 for development of castor (Ricinus communis) hybrid suitable for irrigated and rainfed condition. The castor hybrid GCH 8 (SHB 896) was evaluated in IVHT, AVHT-I and AVHT-II (irrigated and rainfed) along with checks, viz. DCH 177, DCH 519 and GCH 7 at different AICRP (castor) locations during 2013-14 to 2015-16. The hybrid GCH 8 (SHB 896) exhibited wider adaptability and consistent superiority in seed yield and oil yield under irrigated as well as rainfed conditions over checks during the years of evaluation. On the basis of weighted mean, GCH 8 yielded 18.95 q/ha and 35.88 q/ ha over checks, viz. DCH 177, DCH 519, and GCH 7 to the tune of 16.03, 14.02, and 13.01 % & 16.19, 17.64 and 16.57 % higher under rainfed and irrigated condition, respectively. This hybrid also recorded 48.30 % and 48.60 % oil content in seed with extract on an average 9.15 q/ha and 16.37 q/ha oil yield under rainfed and irrigated condition, respectively. This hybrid has profuse branching, tolerance to lodging and resistant to shattering. It was resistant against major diseases like wilt and root rot and showed at par as well as somewhat less attack of major insect pests of castor like semilooper, Spodoptera, leaf hopper, white fly, capsule borer and thrips.